Squamous cell carcinoma with rhabdoid phenotype and osteoclast-like giant cells in a renal-pancreas transplant recipient. - Aljerian, K; Alsaad, K; Chetty, R; Ghazarian, D (2006)
Squamous cell carcinoma (SCC) is the commonest non-melanotic malignant skin tumour encountered after solid-organ transplantation. In this setting it is associated with a worse prognosis than sun-damage-induced SCC. Rhabdoid cells and osteoclastic giant cells are infrequently seen in SCC. This case highlights the unusual occurrence of rhabdoid cells and osteoclastic giant cells in a post-transplant SCC.